Metode Analytical Hierarchy Process (AHP) Sebagai Sistem Pendukung Keputusan Penerimaan Karyawan - Safitri Linawati; Ahmad Fauzi; Ainun Zumarniansyah (LPPM Universitas Bina Sarana Informatika, 2022)
The rapid development of technology with the use of computers as a means to assist humans in obtaining information and solving problems, requires software makers to seek optimal innovation in an effort to improve performance both in quantity and quality. Especially for business entities, private companies, agencies that are currently able to make appropriate, fast and accurate decisions. Planning and fulfillment of human resource needs when managed professionally will greatly determine the quality and success of the company. With the above reasons, a decision support system was made using the Analytical Hierachial Process (AHP) method to make it easier to select employee recruitment and get results. 0.215. Followed by education criteria with a weight of 0.189 and the last ability to communicate with a weight of 0.106. The results of the weighting with expert choice were obtained by Aisyah Rahmah with the highest weight of 0.367, then Andini with a weight of 0.316, then Irwan Gumilar with a weight of 0.161, and finally Ardian Natapraja with a weight of 0.157.